The Conditions of Economic Efficiency and Competitiveness of Tourism Enterprises - Koroteeva, Natalia N.; Hasanov, Elnur L.; Mushrub, Vladimir A.; Klochko, Elena N.; Bakharev, Vladimir V.; Shichiyakh, Rustem A. (International Journal of Economics and Financial Issues, 2016)
The transition to a market system of management in Russia has put a lot of tourism enterprises in a predicament when the competition forces them to look for new ways of survival, use of competitive advantages and provision competitiveness of tourism enterprises and their service. As practice shows, many Russian tourism enterprises of are not ready for active competition, for most of them, the management of competitiveness cannot be referred to and does not act as a standalone system or subsystem in the management process. Despite having a large database and various methods of comprehensive analysis of enterprises (both in Russia and abroad), statistics of tourism enterprises do not currently offer their competitiveness assessment methods. The specific questions of measuring and competitiveness forecasting in terms of competitive market of various properties are no quite adequately developed, there are no well-defined method for competitiveness forecasting of various industrial classification enterprises. The competitiveness of tourism enterprises in the terms of competitive pressure increase is increasingly predetermined by internal and external competitive advantage o territorial subject. If the formation of internal competitive advantages depends on the competitive potential of tourism enterprise, the effectiveness of its management, the formation of external advantages - on the level of competitiveness of a country, region and industry. Keywords: competitiveness, economical efficiency, tourism JEL Classifications: L26, L82, L83, M31